Aida and Her Mainstream Classroom: A Case Study of a Young English Language Learners Literacy Development - Bambang Yudi Cahyono (TEFLIN, 2003)
This article reports a nine-month study of literacy development of Aida, a young English language learner from Indonesia, who was mainstreamed in a Grade 2 classroom in a primary school in the south-eastern part of Australia. This article initially reviews the literature concerning features of the mainstream classroom conducive for second language learning and for literacy development. Following the presentation of methodological issues, it examines English learning activities in Aidas classroom and highlights her literacy development with examples of her work. The results from this study show that Aida developed literacy skills considered important for her second language and learning development. The variety of English learning activities and the encouraging environment in her classroom contributed much to her literacy development.